INTELLIGENT BLUETOOTH-DRIVEN AUTOMATION:MULTI- SENSOR INTEGRATION FOR REAL-TIME SMART HOME CONTROL - Farhat M. Khan,; Saqib Munawwar,; Syed Saad Ali,; Khurram Iqbal,; Mahrukh Shoaib,; Shumaila Qamar,; Hamza Saleem,; Bilawal Raza, (Spectrum of Engineering Sciences, 2025)
The integration of IoT into smart home systems addresses the growing demand for advanced home automation by enabling adaptive, intelligent decision-making. While contemporary smart homes leverage IoT, existing systems often lack adaptability, leading to inefficiencies in user experience, energy consumption, and security. This study explores the challenges, opportunities, and implications of implementing intelligent-based smart home technology, proposing a framework that utilizes machine learning and computer vision to create systems capable of learning user behaviors, anticipating needs, and optimizing home management in real time. The study highlights the limitations of current technologies, including their inability to dynamically adjust to user preferences and on-demand accessibility. A prototype smart home system was developed, employing algorithms to analyze usage patterns and autonomously manage lighting, temperature, and security. Deployed in real-world settings, the system’s performance was evaluated through user feedback and operational data. Results demonstrated significant improvements in user satisfaction (due to personalized automation), energy efficiency (through optimized resource usage), and security (via proactive threat detection). Additionally, the system’s adaptive capabilities reduced energy waste by intelligently adjusting to occupancy and environmental conditions. This study underscores the transformative potential of AI-driven smart homes, offering a sustainable alternative to conventional systems by prioritizing user-centric design and responsiveness. The findings advocate for broader adoption of intelligent technologies to create homes that not only automate tasks but also evolve with residents’ needs, fostering a more efficient, secure, and comfortable living environment. Ultimately, this research validates AI’s role in redefining human-home interactions, paving the way for future innovations in smart living solutions.